2018
DOI: 10.1073/pnas.1811006115
|View full text |Cite
|
Sign up to set email alerts
|

Structural and thermodynamic limits of layer thickness in 2D halide perovskites

Abstract: In the fast-evolving field of halide perovskite semiconductors, the 2D perovskites (A′)2(A)n−1MnX3n+1 [where A = Cs+, CH3NH3+, HC(NH2)2+; A′ = ammonium cation acting as spacer; M = Ge2+, Sn2+, Pb2+; and X = Cl−, Br−, I−] have recently made a critical entry. The n value defines the thickness of the 2D layers, which controls the optical and electronic properties. The 2D perovskites have demonstrated preliminary optoelectronic device lifetime superior to their 3D counterparts. They have also attracted fundamental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
307
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(327 citation statements)
references
References 53 publications
19
307
1
Order By: Relevance
“…Figure a shows that n = 1 phase has the lowest formation energy, but we can notice that the formation energies for different values of n are also quite similar. Our calculations agree with reported trend for the experimentally determined energies of formation of (BA) 2 (MA) n −1 Pb n I 3 n +1, which show that the formation energies for structures with an even number of layers are significantly more exothermic than those for odd values of n , i.e., the formation energy of n = 2 is more negative than that of n = 1 and n = 3 …”
Section: Resultssupporting
confidence: 90%
“…Figure a shows that n = 1 phase has the lowest formation energy, but we can notice that the formation energies for different values of n are also quite similar. Our calculations agree with reported trend for the experimentally determined energies of formation of (BA) 2 (MA) n −1 Pb n I 3 n +1, which show that the formation energies for structures with an even number of layers are significantly more exothermic than those for odd values of n , i.e., the formation energy of n = 2 is more negative than that of n = 1 and n = 3 …”
Section: Resultssupporting
confidence: 90%
“…Either in films, powders, or single crystals, the thickest 2D perovskite thoroughly characterized is an n= 7 perovskite, and there is indirect evidence for an n= 9 phase. In fact, for the family of compounds (BA) 2 (MA) n −1 Pb n I 3n+1 , it has been shown that compounds with n >7 have unfavorable enthalpies of formation . Consequently, claims of 2D perovskites with n values greater than seven should be taken judiciously, as those would be in all likelihood mixed and/or passivated phases.…”
Section: Layered Perovskitesmentioning
confidence: 99%
“… Bandgap and PL energy of the (BA) 2 (MA) n −1 Pb n I 3 n +1 family of perovskites as a function of n. n= ∞ values corresponds to MAPbI 3 . Data obtained from .…”
Section: Propertiesmentioning
confidence: 99%
“…Entirely layered 2D perovskite structures are built by sequential quantum wells with the chemical formula normalA2normalAn1normalMnnormalX3n+1, in which A denotes a long chain of organic molecules, A is a disordered small organic cation in the 3D framework, M and X represent a divalent metal cation and a halide anion, respectively, and n determines the number of layers of the octahedral MX42. The structures feature strong quantum and dielectric confinements, leading to relatively larger bandgaps and binding energies depending on the value of n . Due to the enhancement of the binding energies for electron–hole recombination, they were more preferentially applied for perovskite light‐emitting devices (PeLEDs) at the beginning .…”
Section: Introductionmentioning
confidence: 99%